Community sustainability discussion and strategy session - Griswold, Wendy; Dickinson, Torry; Wigfall, LaBarbara (Kansas State University, 2011)
The shift to sustainable communities requires the involvement of multiple stakeholders in making and implementing decisions and solutions. The decisions that individuals, communities and policy makers are facing often involve highly complex scientific, economic, and social factors. To make strategic policy and planning decisions that address local needs, communities and policy makers must have a solid understanding of sustainability and their role in prioritizing, choosing, and implementing solutions. Colleges and universities are well suited to provide communities and policy makers with the information and capacities needed to participate in decision-making regarding climate change and sustainable practices. The purpose of the Discussion and Strategy Session is to convene a higher education group interested in developing a model for community sustainability approaches and practices. The three pillars of sustainability will be introduced by representatives from environmental, economic, and social disciplines, with a focus on community development. The purpose of the panel is to begin to develop a common language/context for interdisciplinary action around community sustainability. Following these brief presentations, presenters and the audience will participate in a facilitated discussion to explore ways that higher education institutions in Kansas can work collaboratively address community needs related to sustainability issues. The goal is to develop a strategy/action plan for continued work beyond the conference.
Keywords: Economic Sustainability; Democratic Participation; Democratic Education; Cultural; Sustainable Society